Modulation of Innate Immune Signaling Pathways by Herpesviruses - Qizhi Liu; Youliang Rao; Mao Tian; Shu Zhang; Pinghui Feng (Viruses, 2019)
Herpesviruses can be detected by pattern recognition receptors (PRRs), which then activate downstream adaptors, kinases and transcription factors (TFs) to induce the expression of interferons (IFNs) and inflammatory cytokines. IFNs further activate the Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway, inducing the expression of interferon-stimulated genes (ISGs). These signaling events constitute host innate immunity to defeat herpesvirus infection and replication. A hallmark of all herpesviruses is their ability to establish persistent infection in the presence of active immune response. To achieve this, herpesviruses have evolved multiple strategies to suppress or exploit host innate immune signaling pathways to facilitate their infection. This review summarizes the key host innate immune components and their regulation by herpesviruses during infection. Also we highlight unanswered questions and research gaps for future perspectives.